Contemporary Didactic Methodologies in the Teaching of Mathematics in Higher Education: A Systematic Literature Review (2020–2025) - Gómez-García, Brayan (Darul Yasin Al Sys, 2025)
This study analyzes contemporary didactic methodologies applied to the teaching of mathematics in higher education within the Spanish-speaking context. Using a systematic literature review, peer-reviewed studies published between 2020 and 2025 were identified and assessed, focusing on innovative approaches such as problem-based learning, cooperative learning, gamification, flipped classroom, AI-supported instruction, and socio-emotional education. Strict inclusion criteria were applied to ensure quality, considering only full-text articles written in Spanish. The findings indicate that active methodologies significantly improve student motivation, critical thinking, autonomy, and conceptual understanding of mathematics. The incorporation of technological tools, including Python and AI-based platforms, enhances personalized learning, while socio-emotional strategies help reduce math anxiety and strengthen interpersonal competencies. Nonetheless, challenges remain, including the digital divide, resistance to pedagogical change, and the need for specialized teacher training. The study concludes that the convergence of active strategies, emerging technologies, and humanistic approaches offers a transformative opportunity for mathematics education in higher education. Realizing this potential requires supportive educational policies that promote equitable resource access, continuous professional development, and curricular adaptation aligned with 21st-century demands. Further longitudinal and context-specific studies are recommended to assess the long-term effectiveness of these methodologies.